Construction and application of exercise program based on enhanced recovery after surgery in patients undergoing oral and maxillofacial free flap reconstruction surgery after tumor resection (口腔颌面部游离皮瓣修复重建术后早期活动方案的构建及应用效果探讨) - WANG Liangya (王靓雅); ZHAI Haixin (翟海昕); DONG Chen (董晨); CUI Yanan (崔亚楠); GUO Jinnan (郭劲男); ZHANG Wei (张伟); JIANG Siming (姜思明); WANG Jinnan (王金娜); LIU Tianqi (刘天奇); YANG Longfei (杨龙飞); SHI Yanping (史妍萍) (中西医结合护理)
Objective To construct an exercise program based on enhanced recovery after surgery in patients undergoing oral and maxillofacial free flap reconstruction surgery after tumor resection, and investigate its effect on the improvement of clinical outcomes. Methods According to the time of hospital admission, 46 patient (hospital admission between Jan 2017 and December 2019) undergoing oral and maxillofacial free flap reconstruction surgery after tumor resection were included in the control group, receiving routine nursing interventions during perioperative period; 46 patient (hospital admission between Jan 2020 and December 2023) undergoing oral and maxillofacial free flap reconstruction surgery after tumor resection were included in the study group, receiving routine nursing interventions and early exercise program based on the enhanced recovery after surgery. The survival rate of skin flaps, length of hospital stay, length of bedridden period, and incidence of postoperative complications such as lower limb venous thrombosis, pressure injuries and hypostatic pneumonia were compared between two groups. Results There was no significant difference in survival rate of skin flaps between two groups (P＞0. 05). The incidence of hypostatic pneumonia in the study group was lower than that in the control group(P＜0. 01). The length of bedridden period in the study group was shorter than that in the control group(P＜0. 01). There was no significant difference in total length of hospital stay, incidence of lower limb venous thrombosis and pressure injuries between two groups(P＞0. 05). Conclusion The exercise program based on enhanced recovery after surgery is effective to reduce the hypostatic pneumonia after surgery and accelerate the process of postoperative recovery. (目的 基于加速康复外科(ERAS)理念构建口腔颌面部恶性肿瘤根治性切除同期游离皮瓣修复术后早期活动方案, 并探讨其对于改善患者临床结局的影响。方法 选取北京市某三级甲等医院2017年1月—2019年12月行口腔颌面部肿瘤根治性切除联合游离皮瓣移植修复手术的46例患者为对照组, 应用常规围术期护理措施; 选取2020年1月—2023年12月收治的82例患者为研究组, 应用基于ERAS理念的围手术期护理方案, 制订并实施早期活动方案。比较两组患者皮瓣成活率、住院时间、卧床时间及术后并发症(下肢静脉血栓、压力性损伤、坠积性肺炎)的发生情况。结果 两组皮瓣成活率比较, 差异无统计学意义(P＞0. 05)。研究组坠积性肺炎的发生率低于对照组, 卧床时间短于对照组, 差异有统计学意义(P＜0. 01)。两组总体住院时间、下肢静脉血栓及压力性损伤的发生率比较, 差异无统计学意义(P＞0. 05)。结论 基于ERAS理念的早期活动方案可减少口腔颌面部游离皮瓣修复重建术后患者坠积性肺炎的发生风险, 加速术后康复进程。)